Race, ethnicity, and social change: the democratization of middle-class crime - Benson, Michael L. (Criminology, 2021)
Since the mid-1970s, the percentage of non-White people convicted of white-collar type crimes in the federal judicial system has been growing steadily. In 2015, non-Whites accounted for more than half of all convictions for certain white-collar type crimes, but the increase in non-White participation has not occurred evenly across all race and ethnic groups. Asians and Latinos have increased their participation in white-collar crime more so than Blacks. Using data from the U.S. Sentencing Commission, the Equal Employment Opportunity Commission, and the U.S. Census, we investigate whether the differential increase among race and ethnic groups in white-collar type crimes can be explained by their differential increase in middle-class occupations. The findings have implications for opportunity, cultural, and race-centered perspectives on crime, as well as institutional anomie theory, and they suggest that low-level white-collar crimes are being democratized along lines of race and ethnicity.